HUBUNGAN PENGETAHUAN GIZI IBU DAN PENDAPATAN KELUARGA DENGAN PEMBERIAN MP-ASI DINI PADA BAYI USIA 0-6 BULAN DI WILAYAH KERJA PUSKESMAS RAHIA KECAMATAN GU KABUPATEN BUTON TENGAH - Banudi, La; Hikmandayani; Gani , Kameriah (Jurnal Stunting Pesisir dan Aplikasinya, 2024)
Based on preliminary study data obtained from Rahia Community Health Center. Some mothers who have babies aged 0-6 months show that in 2020 the prevalence was 65% giving early MP-ASI and 35% exclusively breastfed, whereas in 2021 the prevalence was 50%. Which provides early MP-ASI and 50% exclusive breast milk. This study aims to determine the relationship between maternal nutritional knowledge and family income with early MP-ASI provision at the Rahia health center, Gu subdistrict, Central Buton district. Method: This research is an analytical survey research. The research design used was a cross sectional study. The population and sample of this study were all mothers who had babies aged 0-6 months. The sampling technique used was the Slovin formula while the statistical test used was chi-square. Results: Based on the research results, the statistical test obtained a value of p = 0.014, which means there is a relationship between maternal nutritional knowledge and the provision of Early MP-ASI in the working area of Puskesamas Rahia, Gu District, Central Buton Regency, and from the results of the statistical test, a value of p = 0.001 was obtained, meaning there is a relationship between family income and early MP-ASI provision in the working area of the Rahia Community Health Center, Gu District, Central Buton Regency. Suggestion: It is hoped that mothers at posyandu in Rahia, Kamama Mekar and Wakeakea villages who have babies aged 0-6 months will pay more attention to giving early MP-ASI appropriate to their age, and it is hoped that mothers will tell caregivers to pay attention to giving early MP-ASI.